2022
DOI: 10.3389/fphar.2022.773454
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prescription Medication Sharing Among Adults in South Korea: A Cross-Sectional Survey

Abstract: Background: Prescription medication sharing is an inappropriate medication use behavior that can lead to medication errors and adverse drug events, posing a public health threat. The reported prevalence of prescription medication lending and borrowing varies by country, ranging from 6%–23% and 5%–52%, respectively. However, research on medication sharing is scant in Asian countries. Therefore, this study aimed to describe the rate of prescription medication sharing practices and investigate the associated beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…Seven studies were from the US (eight papers), 5 , 9 , 17 21 , 36 three from New Zealand (four papers), 8 , 22 24 one study each from Croatia (three papers), 25 27 Saudi Arabia, 28 Malaysia, 29 Nigeria, 30 Philippines, 31 Australia, 32 Ireland, 33 South Korea, 34 and Uganda. 35 Seventeen studies employed quantitative methods, 5 , 9 , 17 31 , 33 36 one was qualitative, 8 and one mixed methods.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven studies were from the US (eight papers), 5 , 9 , 17 21 , 36 three from New Zealand (four papers), 8 , 22 24 one study each from Croatia (three papers), 25 27 Saudi Arabia, 28 Malaysia, 29 Nigeria, 30 Philippines, 31 Australia, 32 Ireland, 33 South Korea, 34 and Uganda. 35 Seventeen studies employed quantitative methods, 5 , 9 , 17 31 , 33 36 one was qualitative, 8 and one mixed methods.…”
Section: Resultsmentioning
confidence: 99%
“… 8 , 29 Of the studies that provided details: fifteen studies reported that painkillers were commonly shared. 9 , 17 28 , 30 , 32 , 34 36 twelve antibiotics; 9 , 18 24 , 28 , 30 , 31 , 33 35 nine allergy medication; 18 24 , 28 , 34 36 five antidepressants/anxiety/mood medication; 9 , 18 , 20 , 21 , 30 , 32 three medications for skin problems and acne; 18 , 20 , 21 , 30 three contraceptives; 18 , 20 , 21 , 33 three sleeping medication/sedatives; 5 , 17 , 36 two asthma medications; 19 , 22 , 23 two blood pressure medication; 9 , 32 and only one study reported the prevalence of sharing each of heart disease medication, 32 diabetes medication, 32 arthritis/joint inflammation medication, 32 cold/flu medication, 30 and stimulants. 17 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations